2011
DOI: 10.5993/ajhb.35.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Using the Web to Increase Physical Activity in College Students

Abstract: Objective: To evaluate the effectiveness of a theoretically based and Web-delivered intervention using common course technology for increasing physical activity in a college student sample. Methods: One hundred four students randomly participated in either a Web-based intervention involving 7 theory-based learning lessons or a control group that received minimal physical activity information. Participants reported levels of physical activity and social cognitive theory (SCT) constructs at baseline and after 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 18 publications
(23 reference statements)
1
50
0
1
Order By: Relevance
“…25 The most frequently used self-report measures were the International Physical Activity Questionnaire (n = 12), Godin Leisure Time Exercise Questionnaire (n = 8), Seven-Day Physical Activity Recall (n = 8), Paffenbarger Physical Activity Questionnaire (n = 6), and the Active Australia Survey (n = 4). Additionally, 4 studies incorporated an aerobic fitness outcome (eg, submaximal treadmill test or walk test), 37,59,66,69 and 3 studies did not specify the measure used to assess physical activity. 59,81,85 …”
Section: Resultsmentioning
confidence: 99%
“…25 The most frequently used self-report measures were the International Physical Activity Questionnaire (n = 12), Godin Leisure Time Exercise Questionnaire (n = 8), Seven-Day Physical Activity Recall (n = 8), Paffenbarger Physical Activity Questionnaire (n = 6), and the Active Australia Survey (n = 4). Additionally, 4 studies incorporated an aerobic fitness outcome (eg, submaximal treadmill test or walk test), 37,59,66,69 and 3 studies did not specify the measure used to assess physical activity. 59,81,85 …”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with results from earlier reviews (van den Berg et al, 2007; Vandelanotte et al, 2007) and meta-analyses (Davies et al, 2012). However, these encouraging results are somewhat limited in that we were unable to identify any Internet-based physical activity intervention studies focused on racial/ethnic minority groups and have identified only one study to date with a majority (78%) Latino sample (Magoc, Tomaka, & Bridges-Arzaga, 2011). To address this disparity, our research team developed and tested an internet-based physical activity intervention for Latinas (Marcus et al, 2015) which found encouraging results after the six-month active intervention phase (Marcus et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…diet, exercise, weight) has been demonstrated previously. 14,15 Many health-related online intervention trials have also been conducted to assess effectiveness of different interventions. [16][17][18] Various software programs are currently available to develop and to implement online interventions, and investigators use different approaches to deliver online interventions and maintain communication with their participants.…”
Section: Introductionmentioning
confidence: 99%